Additive impacts of deoxygenation and acidification threaten marine biota - Alexandra Steckbauer; Shannon G. Klein; Carlos M. Duarte (Global Change Biology, 2020)
Deoxygenation in coastal and open‐ocean ecosystems rarely exists in isolation but occurs concomitantly with acidification. Here, we first combine meta‐data of experimental assessments from across the globe to investigate the potential interactive impacts of deoxygenation and acidification on a broad range of marine taxa. We then characterize the differing degrees of deoxygenation and acidification tested in our dataset using a ratio between the partial pressure of oxygen and carbon dioxide ( p O 2 / p CO 2 ) to assess how biological processes change under an extensive, yet diverse range of p O 2 and p CO 2 conditions. The dataset comprised 375 experimental comparisons and revealed predominantly additive but variable effects (91.7%, additive; 6.0%, synergistic; and 2.3%, antagonistic) of the dual stressors, yielding negative impacts across almost all responses examined. Our data indicate that the p O 2 / p CO 2 ‐ratio offers a simplified metric to characterize the extremity of the concurrent stressors and shows that more severe impacts occurred when ratios represented more extreme deoxygenation and acidification conditions. Importantly, our analysis highlights the need to assess the concurrent impacts of deoxygenation and acidification on marine taxa and that assessments considering the impact of O 2 depletion alone will likely underestimate the impacts of deoxygenation events and their ecosystem‐wide consequences.